2019
DOI: 10.2196/14537
|View full text |Cite
|
Sign up to set email alerts
|

Connected Health User Willingness to Share Personal Health Data: Questionnaire Study

Abstract: BackgroundConnected health has created opportunities for leveraging health data to deliver preventive and personalized health care services. The increasing number of personal devices and advances in measurement technologies contribute to an exponential growth in digital health data. The practices for sharing data across the health ecosystem are evolving as there are more opportunities for using such data to deliver responsive health services.ObjectiveThe objective of this study was to explore user attitudes to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
5
24
1
Order By: Relevance
“…Previous research on people’s willingness to share health data digitally has focused on one particular factor, such as the purpose of data sharing [ 6 , 7 ]. In addition, these studies in this area have been constrained by a specific context, such as looking at data movement within a health care setting [ 8 , 13 , 14 ]. To our knowledge, no studies have investigated how individuals’ preferences change depending on the context in which health data are used, what type of information is involved, which different control mechanisms are considered appropriate for different contexts, and how an individual’s acceptance of sharing data might change in response to changing contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on people’s willingness to share health data digitally has focused on one particular factor, such as the purpose of data sharing [ 6 , 7 ]. In addition, these studies in this area have been constrained by a specific context, such as looking at data movement within a health care setting [ 8 , 13 , 14 ]. To our knowledge, no studies have investigated how individuals’ preferences change depending on the context in which health data are used, what type of information is involved, which different control mechanisms are considered appropriate for different contexts, and how an individual’s acceptance of sharing data might change in response to changing contexts.…”
Section: Introductionmentioning
confidence: 99%
“…However, people are still reluctant to share their PHD for various reasons including privacy concerns, fear of discrimination, and the potential abuse of their data for commercial gain [1][2][3]. Peoples' willingness to share their PHD changes depending on the sensitivity of the data, the purpose of its use, the trustworthiness of the users, and the type of data and its safety [3][4][5]. Indeed, previous studies reported a higher willingness to share PHD with researchers rather than commercial entities [2][3][4][5] and indicated that people are willing to share their data when there is a clear public benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Peoples' willingness to share their PHD changes depending on the sensitivity of the data, the purpose of its use, the trustworthiness of the users, and the type of data and its safety [3][4][5]. Indeed, previous studies reported a higher willingness to share PHD with researchers rather than commercial entities [2][3][4][5] and indicated that people are willing to share their data when there is a clear public benefit. In addition, people are more reluctant to share sensitive health data, i.e., data that carries high personal risks if disclosed [1,5], and need to know that regulatory and technical safeguards exist when sharing their PHD [3].…”
Section: Introductionmentioning
confidence: 99%
“…The most common reason was "lack of regulations". This is a common ethical issue that faces research in most developing countries [34][35][36] which may be resolved by institutional initiatives. The second most common reason was the opinion that data should not be available to the public, which could be solved by providing more orientation to researchers about the importance as well as advantages of data sharing.…”
Section: Discussionmentioning
confidence: 99%